The Influence of Fruiting Plants on the Distribution of Tantalus Monkey (Chlorocebus tantalus tantalus) of Ngel Nyaki Forest Reserve, Taraba State, Nigeria - David, Delphine Leila; James, Fred; Garkida, David Musa; J, Julius Yani (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study investigates the influence of fruiting plants on the distribution of Tantalus monkeys (Chlorocebus tantalus tantalus) in the Ngel Nyaki Forest Reserve, Taraba State, Nigeria. The research aims to determine the diversity, abundance, and distribution of fruiting tree species and their relationship with the spatial patterns of Tantalus monkeys across different habitat types. Data were collected over an eight-month period, covering both dry and wet seasons, using direct field observations and ecological survey methods to assess the availability of fruiting trees, primate feeding preferences, and monkey distribution. Results indicate that the presence and abundance of specific fruiting species significantly affect the distribution patterns of Tantalus monkeys, with seasonal fluctuations in fruit availability influencing primate movement and habitat utilization. This study highlights the critical role of fruiting plants in primate ecology and underscores the importance of conserving fruit-bearing tree species to support sustainable primate populations. The findings provide valuable insights for biodiversity conservation efforts and management strategies in montane forest ecosystems.